2020
DOI: 10.1177/2050313x20944308
|View full text |Cite
|
Sign up to set email alerts
|

Thrombotic microangiopathy following hump-nosed viper ‘Hypnale’ envenomation

Abstract: The hump-nosed vipers which compromise ‘ Hypnale hypnale’, ‘H. zara’ and ‘H. nepa’ have been highly venomous snakes and ‘H. zara’ and ‘H. nepa’ are indigenous to Sri Lanka and ‘H. hypnale’ is endemic to Sri Lanka and India. The clinical presentations range from local swelling, blistering and necrosis at the site of bite with distinct fang marks to systemic envenomations such as coagulopathy, thrombotic microangiopathy, acute kidney injury and death in severe cases. Here, we report a case of thrombotic microang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Its sensitivity can be improved to 80% when the test is performed under standardized conditions [ 23 ]. The need for an alternative bedside test which addresses its shortcomings has been highlighted [ 24 ]. We have previously demonstrated that EXTEM-CT in ROTEM has a 93% sensitivity and 92% accuracy in detecting Russell’s viper envenoming over WBCT20 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its sensitivity can be improved to 80% when the test is performed under standardized conditions [ 23 ]. The need for an alternative bedside test which addresses its shortcomings has been highlighted [ 24 ]. We have previously demonstrated that EXTEM-CT in ROTEM has a 93% sensitivity and 92% accuracy in detecting Russell’s viper envenoming over WBCT20 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antivenom available in Sri Lanka is sourced from India and is effective in envenomation by Indian species of Naja naja , Bungarus caeruleus , Daboia russelii and Echis carinatus . The lack of efficacy of this polyvalent antivenom in HNV has been shown in many studies [ 6 , 17 , 24 ]. Despite this, many physicians use this antivenom in HNV bites [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“… 20 TMA associated with snake bites such as hump-nosed pit viper (Genus: Hypnale ), Russell’s viper ( Daboia russelii ), lowland viper ( Proatheris superciliaris ), Australian brown snake ( Pseudonaja ) and coastal taipan snake ( Oxyuranus ) and Saharan horned viper ( Cerastes cerastes ) has been described in the literature. 17 , 22 26 …”
Section: Discussionmentioning
confidence: 99%
“…20 TMA associated with snake bites such as hump-nosed pit viper (Genus: Hypnale), Russell's viper (Daboia russelii), lowland viper (Proatheris superciliaris), Australian brown snake (Pseudonaja) and coastal taipan snake (Oxyuranus) and Saharan horned viper (Cerastes cerastes) has been described in the literature. 17,[22][23][24][25][26] Plasma exchange has a role in the treatment of TMA following snake bite. It decreases the further endothelial damage of blood vessels and normalizes the coagulation cascade and platelet aggregation via removal of toxins from blood.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Acute tubular necrosis is the most common cause of AKI (80%), followed by interstitial nephritis (15%) and, more rarely, thrombotic microangiopathy (TMA) (approximately 5% of cases). 8,9 The species involved in the development of TMA are Hypnale hypnale, [10][11][12][13] Pseudonaja spp, 14 Notechis scutatus, 15 Daboia russellii, 16,17 Bothrops jararaca, 18,19 Echis coloratus, 20,21 Bothrops erythromelas, 22 and Bothrops lanceolatus. 23 Some cases of TMA may progress to renal cortical necrosis.…”
Section: Introductionmentioning
confidence: 99%